Zm401, a short-open reading-frame mRNA or noncoding RNA, is essential for tapetum and microspore development and can regulate the floret formation in maize - Ma, Jinxia; Yan, Bingxue; Qu, Yanying; Qin, Fangfang; Yang, Yantao; Hao, Xiujing; Yu, Jingjuan; Zhao, Qian; Zhu, Dengyun; Ao, Guangming (Journal of cellular biochemistry, 2008)
In flowering plants, pollen formation depends on the differentiation and interaction of two cell types in the anther: the reproductive cells, called microsporocytes, and somatic cells that form the tapetum. Previously, we cloned a pollen specific gene, zm401, from a cDNA library generated from the mature pollen of Zea mays. Expression of partial cDNA of zm401 in maize and ectopic expression of zm401 in tobacco suggested it may play a role in anther development. Here we present the expression and functional characterization of this pollen specific gene in maize. Zm401 is expressed primarily in the anthers (tapetal cells as well as microspores) in a developmentally regulated manner. That is, it is expressed from floret forming stage, increasing in concentration up to mature pollen. Knockdown of zm401 significantly affected the expression of ZmMADS2, MZm3‐3, and ZmC5, critical genes for pollen development; led to aberrant development of the microspore and tapetum, and finally male‐sterility. Zm401 possesses highly conserved sequences and evolutionary conserved stable RNA secondary structure in monocotyledon. These data show that zm401 could be one of the key growth regulators in anther development, and functions as a short‐open reading‐frame mRNA (sORF mRNA) and/or noncoding RNA (ncRNA). J. Cell. Biochem. 105: 136–146, 2008. © 2008 Wiley‐Liss, Inc.